2020
DOI: 10.3390/ijms21155205
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B*44 and C*01 Prevalence Correlates with Covid19 Spreading across Italy

Abstract: The spread of COVID-19 is showing huge, unexplained, differences between northern and southern Italy. We hypothesized that the regional prevalence of specific class I human leukocyte antigen (HLA) alleles, which shape the anti-viral immune response, might partly underlie these differences. Through an ecological approach, we analyzed whether a set of HLA alleles (A, B, C), known to be involved in the immune response against infections, correlates with COVID-19 incidence. COVID-19 data were provided by the Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 39 publications
3
89
2
1
Order By: Relevance
“…According to the results, the prevalence of the HLA-C*01 and HLA-B*44 alleles are predictive of the incidence of COVID-19 in the different Italian regions and therefore confer susceptibility to SARS-CoV-2 infection (34). This association was not observed in the Sardinian population, probably because the HLA-C*01 and HLA-B*44 alleles, while being fairly common in the north eastern areas of Italy, are scarcely represented in the central-south (34). In other populations, the HLA-B*44 allele would seem to exert a protective effect (54), as opposite to what was observed by Correale et al (34).…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…According to the results, the prevalence of the HLA-C*01 and HLA-B*44 alleles are predictive of the incidence of COVID-19 in the different Italian regions and therefore confer susceptibility to SARS-CoV-2 infection (34). This association was not observed in the Sardinian population, probably because the HLA-C*01 and HLA-B*44 alleles, while being fairly common in the north eastern areas of Italy, are scarcely represented in the central-south (34). In other populations, the HLA-B*44 allele would seem to exert a protective effect (54), as opposite to what was observed by Correale et al (34).…”
Section: Discussioncontrasting
confidence: 61%
“…This association was not observed in the Sardinian population, probably because the HLA-C*01 and HLA-B*44 alleles, while being fairly common in the north eastern areas of Italy, are scarcely represented in the central-south (34). In other populations, the HLA-B*44 allele would seem to exert a protective effect (54), as opposite to what was observed by Correale et al (34). In our study of the Sardinian population, we found that the HLA-C*04:01 allele conferred susceptibility to SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In addition to HLA-B � 2705, B44 alleles also had very low number of epitopes (17 for B4402 and 19 for B4403, Table 1). A recent epidemiologic study reported that HLA-B � 44 and HLA-C � 01 positive individuals were more susceptible to SARS-CoV-2 infections in Italy when compared with HLA-A � 25, B � 08, B � 15:01, B � 51, B � 14, B � 18, B � 49, and C � 03 [25]. Although we weren't able to predict the epitopes for C � 01 allele as it hasn't been enlisted in NetMHC 4.0, each of A � 25, B � 08, B � 15:01, B � 51, B � 14, B � 18 and B � 49 alleles we analyzed showed higher numbers of CD8 T cell epitopes than B � 44 (Table 1), indicating broad anti-S protein CD8 T cell responses may provide better protection against SARS-CoV-2 infection.…”
Section: Plos Onementioning
confidence: 99%
“…Further supporting T cell importance, in silico predictions and epidemiologic studies suggest that COVID-19 vulnerability may depend on the HLA haplotype of a person and its capacity to present SARS-CoV-2 epitopes to T cells. In Italy, prevalence of the potentially permissive alleles HLA-B * 44 and C * 01 correlates with COVID-19 spread (41,42).…”
Section: The Case For T Cellsmentioning
confidence: 99%